Comparison of major appendicitis scoring systems on the clinical-histopathological correlation - Sezgin Uludag, Server; Esin Tecan Sanli, Deniz; Ali Yucesoy, Mehmet; Gures, Nazim; Necati Sanli, Ahmet; Ipekci, Afsin; Kagan Zengin, Abdullah (Annals of Medical Research, 2021)
Aim: We aimed to investigate the predictive value of the four most popular scoring systems, such as Modified Alvarado, Raja Isteri Pengiran Anak Saleha Appendicitis, Tzanakis, and Lintula, for histopathologically proven acute, phlegmonous, and gangrenous/perforated appendicitis. Materials and Methods: We retrospectively reviewed the results of 239 patients who underwent appendectomy between 2016 and 2019 in our department. The patients’ demographic data, surgery method, histopathological results of the specimens (uncomplicated acute appendicitis, phlegmonous, and gangrenous/perforated appendicitis) were recorded. The predictivity of Modified Alvarado, Raja Isteri Pengiran Anak Saleha Appendicitis, Tzanakis, and Lintula scoring systems according to the histopathological results was compared.Results: The modified Alvarado scoring system showed statistically significant efficacy in the preoperative distinction of acute, phlegmonous, and gangrenous/perforated appendicitis. Although the Raja Isteri Pengiran Anak Saleha Appendicitis and Tzanakis score systems are effective in acute and gangrenous/perforated differentiation, they did not show statistically significant efficacy between acute and phlegmonous appendicitis. The Lintula scoring system was the weakest among the four and did not show statistically significant efficacy in the distinction of all three diagnoses.Conclusion: The diagnosis of acute appendicitis is easier with the use of scoring systems. Scoring systems can also help signal advanced stage and complicated forms of acute appendicitis, such as phlegmonous and gangrenous/perforated appendicitis. The modified Alvarado was the most correlated scoring system with histopathological results.